2014
DOI: 10.4103/0970-9185.137272
|View full text |Cite
|
Sign up to set email alerts
|

A prospective controlled study to assess the antiemetic effect of midazolam following intragastric balloon insertion

Abstract: Background and Aims:Obesity is a chronic disease with considerable morbidity and mortality. The intragastric balloon appears attractive for a group of patients who do not respond to medical therapy and who are not surgical candidates. Postoperative nausea and vomiting (PONV) are distressing adverse effects for these patients. Midazolam has been used as an antiemetic, both as a preventive or rescue medication. The study aims at studying effect of combined use of ondansetron and midazolam to decrease the PONV fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The first study compared a therapeutic regimen of midazolam and ondansetron vs ondansetron alone for preventive treatment of nausea/vomiting and found that combination therapy of midazolam and ondansetron trended toward outperforming ondansetron alone (RR, 0.57; 95% CI, 0.32-1.02). 10 Further, early balloon removal rate was lower in the midazolam and ondansetron arm compared with the ondansetron-alone arm (0 of 29 and 3 of 28, respectively; RR, 0.14; 95% CI, 0.01-2.56). The second study compared mean vomiting incidence among alizapride, tropisetron, and tropisetron with droperidol, but due to limited availability of these agents in the United States, it was not applied to this recommendation.…”
Section: Very Lowmentioning
confidence: 86%
“…The first study compared a therapeutic regimen of midazolam and ondansetron vs ondansetron alone for preventive treatment of nausea/vomiting and found that combination therapy of midazolam and ondansetron trended toward outperforming ondansetron alone (RR, 0.57; 95% CI, 0.32-1.02). 10 Further, early balloon removal rate was lower in the midazolam and ondansetron arm compared with the ondansetron-alone arm (0 of 29 and 3 of 28, respectively; RR, 0.14; 95% CI, 0.01-2.56). The second study compared mean vomiting incidence among alizapride, tropisetron, and tropisetron with droperidol, but due to limited availability of these agents in the United States, it was not applied to this recommendation.…”
Section: Very Lowmentioning
confidence: 86%
“…In 2007, Lee et al found that 2 mg of midazolam was as good as 4 mg of ondansetron for PONV prophylaxis in female non‐smoking patients 15 . Most of the current literature, however, focuses on the effect of addition of midazolam to antiemetic agents like 5HT3 antagonists, dexamethasone and haloperidol 8,16,17 . Kim and co‐workers reported that midazolam provided better PONV prophylaxis than ondansetron and that the combination of ondansetron and midazolam was more effective in reducing PONV (33.3% vs 63.3% with ondansetron and 46.7% with midazolam) 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative details in the two groups addition of midazolam to antiemetic agents like 5HT3 antagonists, dexamethasone and haloperidol. 8,16,17 Kim and co-workers reported that midazolam provided better PONV prophylaxis than ondansetron and that the combination of ondansetron and midazolam was more effective in reducing PONV (33.3% vs 63.3% with ondansetron and 46.7% with midazolam). 5 Similarly, Park and colleagues, in their study on 126 patients undergoing laparoscopic gynaecological surgeries, reported that incidence of complete response was around 70% with a combination of midazolam and ramosetron while it was 44% with ramosetron alone.…”
Section: Ta B L Ementioning
confidence: 99%
“…Fortunately, the complications were all minor and most of them were self-healing reactions which would disappear after a few days. In the meaning time, some researches [ 29 31 ] were committed to improving these conditions by developing new balloons or new placement techniques as well as by associating with other treatment such as antiemetic. Although some serious complications such as gastric-intestinal perforation or intestinal obstruction were not reported in this review, it should be noted that there were some trials meeting these reactions [ 10 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%